Acute, prolonged and persistent diarrhea in children and its difference with chronic diarrhea - Enrique Antonio González Corona (Centro Provincial de Información de Ciencias Médicas, 2017)
On the base of 55 years experience in the treatment of children with acute diarrhea and the updating of the knowledge acquired in the last decades in the Control Program for the Diarrheal disease of World Health Organization, it was decided to review the definitions of the different clinical types of this disorder and its differentiation with chronic diarrhea.  Thus, some important aspects are offered such as the factors which prolong the common acute diarrhea, the use of antibiotics, vaccination against rotavirus, the vicious circle diarrhea-malnutrition, the use of probiotic and biotherapeutic agents, the intestinal bacterial overgrowth and the traveler's diarrhea.  It was concluded that it is necessary to identify early the prolonged diarrhea and to indicate an opportune treatment to avoid its course toward persistent diarrhea, as well as its the negative effect on the growth of small children, which occasionally can cause them death.